Response to HIV-1 gp160-carrying recombinant virus HSV-1 and HIV-1 VLP combined vaccine in BALB/c mice - Zhang, Beibei; Mao, Hongyan; Zhu, Hongjuan; Guo, Jingxia; Zhou, Paul; Ma, Zhenghai (Frontiers in Microbiology, 2023)
Human immunodeficiency virus (HIV) induced AIDS causes a large number of infections and deaths worldwide every year, still no vaccines are available to prevent infection. Recombinant herpes simplex virus type 1 (HSV-1) vector-based vaccines coding the target proteins of other pathogens have been widely used for disease control. Here, a recombinant virus with HIV-1 gp160 gene integration into the internal reverse (IR) region-deleted HSV-1 vector (HSV-BAC), was obtained by bacterial artificial chromosome (BAC) technology, and its immunogenicity investigated in BALB/c mice. The result showed similar replication ability of the HSV-BAC-based recombinant virus and wild type. Furthermore, humoral and cellular immune response showed superiority of intraperitoneal (IP) administration, compared to intranasally (IN), subcutaneous (SC) and intramuscularly (IM). More importantly, in a prime-boost combination study murine model, the recombinant viruses prime followed by HIV-1 VLP boost induced stronger and broader immune responses than single virus or protein vaccination in a similar vaccination regimen. Antibody production was sufficient for viral clearance, along with efficient T-cell activation. Overall, these findings expose the value of combining different vaccine vectors and modalities to improve immunogenicity and breadth against different HIV-1 antigens.